Synthesis, Spectral Characterization and Studies of New Heterocyclic Azo Dye Compound Derived From Imidazole with Some Transition Metal Complexes - Zainab. J. Mohammed (Journal of Global Pharma Technology, 2018)
A new heterocyclic azo ligand (E)-2-((4,5-bis(4-methoxyphenyl)-1H-imidazol-2-yl)diazenyl) benzoic acid, (CPMI=HL) was prepared by coupling diazotized of anthranilic acid with 4,5-bis(4-methoxyphenyl)-1H-imidazole in alkaline ethanolic solution. Eight complexes with Mn(II) , Fe(II), Co(II) ,Ni(II) ,Cu(II) ,Zn(II) ,Cd(II) and Hg(II) ions. These complexes and ligand were characterized by elemental analyses, IR, U.V-Vis spectra, mass spectra, (ligand and its Copper (II) complex), magnetic moments, Atomic absorption and molar conductance measurements. The IR data show that, the azo molecule behaves as a mono negative tridentate(N, N,O) ligand and linked through the carboxlicoxygen atom, azomethanic nitrogen of heterocyclic imidazole molecule and nitrogen atom of azo group, produces colored chelates with transition metal ions.The molar conductance data for all complexes are nonelectrolyte. Based on analytical and spectral data we proposed a monomeric octahedral geometry for all chelate complexes and d2sp3 or sp3d2 hybridization.Keywords: Azo imidazole, Chelate complexes, Characterization.